Seventy Years of Personal Disposable Income and Consumption in Ireland - Stuart, Rebecca (SSISI, 2017)
This paper compiles annual data on personal consumption and personal disposable income for Ireland over the period 1944 to 2014 and goes on to estimate consumption functions. Having established that the series are cointegrated, an error-correction model is estimated which is stable over the entire 70-year period. A dynamic out-of-sample forecast of consumption for the period 2007-2014 fits well although it does not capture the full decline in consumption in 2009. Extensions of the model to include interest rates, household credit, house prices and unemployment as drivers of consumption are discussed.
read before the Society, 19 January 2017
Keywords: Ireland; historical statistics; long time series; permanent income hypothesis; 314.15